From Defensive to Cooperative Sovereignty: International Cooperation in Indonesia’s Territorial Boundary Delimitation under International Law - Darwis, Muhammad; Kastulani, Mohd; Hasibuan, Anwar Saleh; Maruf, Maruf (Kosmik Hukum, 2026)
This study analyses the paradigm shift in the regulation of territorial boundaries and jurisdiction of the Unitary State of the Republic of Indonesia as stipulated in Law No. 43 of 2008 on State Territory. The study focuses on Articles 2, 3, 5, and 14–18 with an International Cooperation approach, which emphasises the importance of shifting from defensive sovereignty to collaborative sovereignty in state border governance. Normatively, this study uses a doctrinal legal analysis method with a conceptual and comparative approach to the principles of international law, particularly the United Nations Convention on the Law of the Sea (UNCLOS). The results of the study indicate that the norms in Law No. 43 of 2008 need to be transformed from an administrative paradigm to a diplomatic-integrative paradigm. The management of state borders not only serves to maintain territorial integrity but also strengthens Indonesia's position as a norm entrepreneur in border diplomacy and regional maritime cooperation. This paradigm shift places international cooperation, mutual benefits, and the principle of equity as the new foundation for the formulation and implementation of state territorial boundary policies. Thus, the concept of state territorial regulation shifts from a closed sovereignty approach to an open, cooperative sovereignty, in line with Indonesia's free and active foreign policy.